Tanduk Prayer in a Traditional Event in Sendangcoyo Village, Lasem District, Rembang Regency: An Ethnolinguistic Study - Yusuf Margono; Dyah Kurnia, Ermi; Miji Lestari, Prembayun (Program Studi Sastra Jawa, Fakultas Bahasa dan Seni, Universitas Negeri Semarang, 2025)
Tanduk is a series of activities carried out before the start of a traditional ceremony to bring blessings. This study uses an ethnolinguistic approach to examine the recitation of tanduk prayers as a verbal expression in the traditional ceremonies of the Sendangcoyo Village community, Lasem Subdistrict, Rembang Regency. The tanduk prayer is a conventional form of speech rich in spiritual, symbolic, and local cultural content. The research method used is qualitative descriptive, with data collection techniques including observation, interviews, and documentation. The primary data consists of the text of the tanduk prayer obtained from local traditional figures, which was then analyzed using an ethnolinguistic approach. The study results indicate that the tanduk prayer has a distinctive linguistic structure, consisting of Javanese krama sentences with a repetitive style. The primary function of this prayer is as a medium for requesting safety and spiritual protection during traditional rituals. Additionally, the tanduk prayer contains local knowledge systems regarding life after death, spiritual hierarchy, and the relationship between humans, nature, and ancestors. Through this tanduk prayer, the community collectively builds awareness of the values of life that have been passed down through generations. Thus, the tanduk prayer is a religious practice and a living archive of the spirituality and cultural identity of the Sendangcoyo community.